The Pink Arche. The First Principle of the Posthuman Reality in the Anthropocene and SUPERFLEX’s "Pink Elements" as a Possible Representation of it - Innocenti, Marco (Studia Germanica Posnaniensia, 2022)
This article will argue the suitability of the Pink Elements (2019) by SUPERFLEX for representing the elementary particles of our posthuman reality, intended from a cultural perspective. Firstly, it will address the ‚bit’, deemed by some as the current arche, revealing its limits in the light of the Niche Construction Theory applied to humans. Then, I will try to demonstrate that the relational dimension corresponds to reality as we perceive it after postmodernity. Therefore, I will analyse the dynamics of the human-environment relationship in the geological era called ‚Anthropocene’ by comparing Merleau-Ponty’s perception and Morton’s hyperobjects. Finally, I will give some examples of recent artworks reflecting this relationship, synthesisable as a ‚recording of a non-deciphered text’, among which the Pink Elements will stand out as bricks capable of representing the ultimate substance of reality as the posthuman culture shows it to us.